LAND SUBSIDENCE ANALYSIS OBSERVED BY PS-INSAR METHOD IN SOUTHERN PART OF BALI, INDONESIA (A CASE STUDY OF DENPASAR AND BADUNG AREA) - Made Ryan Dwiputra; Takahiro Osawa; I Wayan Gede Astawa Karang (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2020)
The utilization of groundwater unwise leads to problems for the life of sentient beings. The majority of environmental damage, mainly by groundwater utilization, is done or caused by human activities. The land subsidence, drought, seawater intrusion are some examples of damage caused by groundwater utilization unwise. This research aims to estimate land subsidence in southern Bali and analyze groundwater level reduction with land subsidence. The PS-InSAR technique to monitor land subsidence has been carried out in several regions in Indonesia and other countries. In this study, 38 images of Sentinel-1 taken from February 2015 to December 2018 are used to analyze the PS-InSAR technique. Land subsidence is found in Denpasar Utara district and Kerobokan district with deformation in -8 mm to -19 mm and velocity up to -5 mm/year. The utilization of groundwater causing land subsidence in Southern Bali is no significant relationship with coefficient correlation 0,16 and influenced only 2,7%. Limited groundwater data also influences the correlation between groundwater utilization and the occurrence of land subsidence. Keywords: Land Subsidence; Sentinel-1A; PS-InSAR; Southern Bali.